2018
DOI: 10.1039/c8fo00248g
|View full text |Cite
|
Sign up to set email alerts
|

Oleuropein and hydroxytyrosol rich extracts from olive leaves attenuate liver injury and lipid metabolism disturbance in bisphenol A-treated rats

Abstract: In the present study, we investigated the protective effects of oleuropein- and hydroxytyrosol-rich extracts obtained from olive leaves against bisphenol A (BPA)-induced hyperlipidemia and liver injury in male rats. For this purpose, four groups of male rats (8 per group) were used: control group (Control), rats treated with BPA, rats treated with both BPA and oleuropein (OLE-BPA), and rats treated with both BPA and hydroxytyrosol (HYT-BPA). After 60 days of treatment, the results obtained using the DXA techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
67
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 58 publications
2
67
2
3
Order By: Relevance
“…In bisphenol A‐treated rats, oleuropein significantly reduced malondialdehyde levels and increased COD and TEAC in both livers and kidneys of rats (A. Mahmoudi et al, ). Another study using bisphenol A also corroborated this in liver tissue and found increased SOD and CAT levels and improved trolox capacity to a level close to the control (A. Mahmoudi et al, ). Furthermore, an extract, rich in oleuropein‐related compounds, was found to protect against DNA damage from heterocyclic amines, which could occur due to development of oxidative stress (Fuccelli et al, ) and could help prevent carcinogenesis through this mechanism.…”
Section: Role Of Oleuropein In Treatment Of Metabolic Syndromementioning
confidence: 70%
See 4 more Smart Citations
“…In bisphenol A‐treated rats, oleuropein significantly reduced malondialdehyde levels and increased COD and TEAC in both livers and kidneys of rats (A. Mahmoudi et al, ). Another study using bisphenol A also corroborated this in liver tissue and found increased SOD and CAT levels and improved trolox capacity to a level close to the control (A. Mahmoudi et al, ). Furthermore, an extract, rich in oleuropein‐related compounds, was found to protect against DNA damage from heterocyclic amines, which could occur due to development of oxidative stress (Fuccelli et al, ) and could help prevent carcinogenesis through this mechanism.…”
Section: Role Of Oleuropein In Treatment Of Metabolic Syndromementioning
confidence: 70%
“…Further, antihyperlipidemic therapy in diabetics proves effective for reducing primary cardiovascular events (Jakob, Nordmann, Schandelmaier, Ferreira‐González, & Briel, ; Rafel et al, ), and increased levels of HDL have been associated with a reduced risk of adverse events (Goldbourt et al, ). Oleuropein has been shown to reduce serum LDL (Jemai et al, 2008; A. Mahmoudi et al, ; Khalili et al, ; Lepore et al, ; F. Hadrich, Garcia, et al, ), TC (Jemai et al, 2008; A. Mahmoudi et al, ; Khalili et al, ; I. Andreadou et al, ; F. Hadrich, Garcia, et al, ; 246, Y. Oi‐Kano et al, ), and serum triglycerides (Jemai et al, 2008; A. Mahmoudi et al, ; Khalili et al, ; I. Andreadou et al, ; F. Hadrich, Garcia, et al, ; Y. Oi‐Kano et al, ) while also increasing serum HDL (Jemai et al, 2008; A. Mahmoudi et al, ; Khalili et al, ; F. Hadrich, Garcia, et al, ). In wild‐type mice, oleuropein caused reduction in serum TG and TC but not in PPAR‐α null mice showing that effect was due to activation and upregulation of PPAR‐α mRNA with an increase in multiple PPAR‐α target genes (Malliou et al, ).…”
Section: Role Of Oleuropein In Treatment Of Metabolic Syndromementioning
confidence: 99%
See 3 more Smart Citations